0259 Reduction of the Apnea-Hypopnea Duration Ameliorates Endothelial Dysfunction, Vascular Inflammation, and Systemic Hypertension in a Rat Model of Obstructive Sleep Apnea. (12th April 2019) - Wu, Hao; Fang, Fang; Wei, Yongxiang
Abstract: Introduction: We aimed to investigate the effect of the apnea-hypopnea duration on obstructive sleep apnea (OSA) and related sequelae in a rat model. Methods: A novel rat model of OSA, including a body container, head cover, air bag, piston, and controller, was used to mimic the main physiological aspects of OSA. Wistar rats were randomized to six groups according to different treatments for 4 weeks: (1) OSA (apnea for 60 s in a 90-s window of breathing [60s/90s] with anesthesia), (2) OSA 30s/90s with anesthesia, (3) partial recovery (60s/90s for 2 weeks, followed by 15s/90s for 2 weeks with anesthesia), (4) complete recovery (60s/90s for 2 weeks with anesthesia, and then normal breathing for 2 weeks), (5) sham (normal breathing in the device with anesthesia), and (6) control group (normal breathing, normal cage, no anesthesia). We recorded blood pressure, endothelial function, left ventricular function, and inflammation at different time points. Results: Vascular inflammation and endothelial dysfunction were observed in OSA models. A longer apnea-hypopnea duration induced worse systemic inflammatory and endothelial dysfunction. Partial and complete recovery reversed vascular inflammation and endothelial dysfunction, and delayed development of hypertension. The left ventricular weight/body weight ratio was significantly higher in the OSA (60s/90s) group compare with complete recovery, sham and control group, which persisted despite partial recovery (p<0.05). Conclusion: A longer apnea-hypopnea duration is related to worse systemic inflammatory and endothelial dysfunction, and hypertension and cardiac remodeling. These side effects can be treated by complete recovery and partial recovery can achieve similar therapeutic effects to complete recovery. These results indicate that time parameters for assessing OSA, such as the apnea-hypopnea duration, should be considered instead of the apnea-hypopnea index. Support (If Any): This study was supported by Beijing Medical Project 2016-4, Beijing Key Laboratory of upper airway dysfunction related cardiovascular diseases (NO: BZ0377).